2015
DOI: 10.1185/03007995.2015.1020364
|View full text |Cite
|
Sign up to set email alerts
|

Review of patient-reported outcome instruments measuring health-related quality of life and satisfaction in patients with type 2 diabetes treated with oral therapy

Abstract: Very few of the existing PRO instruments are specific to OHAs. Despite satisfaction instruments being recommended to differentiate between OHAs in studies of T2DM based on medication attributes, we find that none of the existing instruments appear to be useful in detecting differences between treatments, therefore limiting their use in clinical and observational research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 104 publications
2
35
1
Order By: Relevance
“…This was attributed to success of the removable partial denture (RPD) therapy in both groups; however, better outcomes (lower OHIP-14 score) were obtained among the PA-RPD patients compared to the C-RPD) patients. These results are in line with several studies which used different patients' self-reported measures including the OHIP-14 questionnaire [14,18,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…This was attributed to success of the removable partial denture (RPD) therapy in both groups; however, better outcomes (lower OHIP-14 score) were obtained among the PA-RPD patients compared to the C-RPD) patients. These results are in line with several studies which used different patients' self-reported measures including the OHIP-14 questionnaire [14,18,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 90%
“…However, the outcome of diabetes treatments should not be evaluated only by HbA1c levels as the evaluation of the psychological aspects of patients, including treatment satisfaction, wellbeing and quality of life (QOL), are also important, which are referred to as patient-reported outcomes (PROs) ( Table 1 ) [ 6 , 7 , 8 , 9 ]. The Diabetes Treatment Satisfaction Questionnaire (DTSQ) is a questionnaire used to assess patients’ satisfaction with their diabetes treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment satisfaction and health-related quality of life (HRQOL) are important for successful treatment of diabetes [ 17 ]. It has been reported that improved quality of life (QOL) results in improved adherence with medication [ 18 ] and poor adherence contributes to poor glycemic control [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of 3 subscales, “treatment convenience”, “somatic symptom” and “satisfaction”. The OHA-Q is the only satisfaction instrument that specific to oral hypoglycemic treatment [ 17 ]. It can evaluate treatment satisfaction, including unique side effects to OHA.…”
Section: Introductionmentioning
confidence: 99%